Combination of bioresponsive chelates and perfluorinated lipid nanoparticles enables in vivo MRI probe quantification. Issue 66 (20th July 2020) - Gambino, Giuseppe; Gambino, Tanja; Angelovski, Goran
Abstract : We used lipid nanoparticles with a perfluorinated core as a platform for a responsive nanosized 1 H MRI contrast agent to achieve the in vivo quantification of the probe by means of 19 F MRI. Abstract : We developed a nanosized perfluorocarbon-based system with incorporated paramagnetic Gd(iii ) chelates, able to generate a quantitative 19 F MRI signal, while in parallel capable of modulating the 1 H MRI signal in response to the coordination of Ca 2+ ions. Subsequently, we performed experiments in vivo and estimated the concentration of the applied probe in the tissue by means of 19 F MRI.